2021
DOI: 10.1021/acsbiomaterials.0c01804
|View full text |Cite
|
Sign up to set email alerts
|

Acetobacter Biofilm: Electronic Characterization and Reactive Transduction of Pressure

Abstract: The bacterial skin studied here is a several centimeter-wide colony of Acetobacter aceti living on a cellulose-based hydrogel. We demonstrate that the colony exhibits trains of spikes of extracellular electrical potential, with amplitudes of the spikes varying from 1 to 17 mV. The bacterial pad responds to mechanical stimulation with distinctive changes in its electrical activity. While studying the passive electrical properties of the bacterial pad, we found that the pad provides an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…First, as proposed in [39], the waves of depolarisation, emerging due to metabolically triggered release of potassium, travelling in a bacterial film coordinate the cells’ metabolic states. The excitation wave, recorded as spikes, have been also observed in acetobacter colonies [32, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as proposed in [39], the waves of depolarisation, emerging due to metabolically triggered release of potassium, travelling in a bacterial film coordinate the cells’ metabolic states. The excitation wave, recorded as spikes, have been also observed in acetobacter colonies [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…If kombucha zoogleal mats acted as ‘continuous’ sheets with non-linear electrical properties and endogenous electrical activity the mats would be fertile substrate for future living electronics and computing devices. Pioneer experiments with acetobacter colonies [32, 33] successfully demonstrated that bacterial films can be used for sensing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical properties of kombucha mats can further advance ideas on electricity based integration, and possibly, protocognition of symbiotic organisms [8,9,10,11]. Similar bacterial cellulose mats, for example, produced by Acetobacter aceti colonies, have been shown to feature interesting electrical properties and pressure sensing capabilities [12].…”
Section: Introductionmentioning
confidence: 99%
“…We have already demonstrated a potentially unique properties of kombucha mats via analysis of their electrical potential dynamics [33]. We have also shown that acetobacter colonies, which form thick bacterial films, can be used for sensing purposes [34, 35].…”
Section: Introductionmentioning
confidence: 99%